Results of Statistical Security Assessment of Generators Using M-Ary Codes Based on the NIST 802STS Package - Rzaev, Kh.N.; Bagirov, E.Y.; Mammadov, M.F. (Herald of Azerbaijan Engineering Academy, 2023)
In the article, the research has been carried out on the stability of known algorithms for generating pseudo-random sequences and hashing functions. It is proposed to use the NIST 822STS package to evaluate the statistical security of pseudorandom number generators. The presented results confirm the theoretical results of assessing the resistance of the proposed generators on m-ary codes. The results of a study of the performance of software implementations of generators based on re-dundant block codes and some well-known generators (generator based on FIPS 197, BBS) are pre-sented and showed that the developed algorithms for generating PRN have low computational com-plexity